2017
DOI: 10.1161/jaha.117.006081
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and the Risk of Maternal Cardiovascular Disease: A Prospective Study of 300 000 Chinese Women

Abstract: BackgroundBreastfeeding confers substantial benefits to child health and has also been associated with lower risk of maternal cardiovascular diseases (CVDs) in later life. However, the evidence on the effects of CVD is still inconsistent, especially in East Asians, in whom the frequency and duration of breastfeeding significantly differ from those in the West.Methods and ResultsIn 2004–2008, the nationwide China Kadoorie Biobank recruited 0.5 million individuals aged 30 to 79 years from 10 diverse regions acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 32 publications
2
45
0
1
Order By: Relevance
“…Women who breastfeed have decreased risk for metabolic syndrome (Choi, Kim, Cho, Kim, & Shim, ; Gunderson et al, ; Ram et al, ), Type 2 diabetes mellitus (T2DM; Ip et al, ; Schwarz et al, ; Stuebe, Rich‐Edwards, Willett, Manson, & Michels, ), cardiovascular disease (CVD; Peters et al, ; Schwarz et al, ; Stuebe et al, ), and cancer (Chowdhury et al, ; Ip et al, ) and decreased all‐cause mortality (Bartick et al, ) in later life compared with women who do not breastfeed. Several studies have reported that the degree of maternal health benefit is proportional to lactation intensity and duration, suggestive of a dose–response relationship (Gunderson et al, ; Peters et al, ; Ziegler et al, ). The greatest long‐term maternal health benefits have been shown in women who follow the World Health Organization recommendation for exclusive breastfeeding (EBF) for the first 6 months of life without formula supplementation or introduction of other foods or beverages (Organization, ).…”
Section: Introductionmentioning
confidence: 99%
“…Women who breastfeed have decreased risk for metabolic syndrome (Choi, Kim, Cho, Kim, & Shim, ; Gunderson et al, ; Ram et al, ), Type 2 diabetes mellitus (T2DM; Ip et al, ; Schwarz et al, ; Stuebe, Rich‐Edwards, Willett, Manson, & Michels, ), cardiovascular disease (CVD; Peters et al, ; Schwarz et al, ; Stuebe et al, ), and cancer (Chowdhury et al, ; Ip et al, ) and decreased all‐cause mortality (Bartick et al, ) in later life compared with women who do not breastfeed. Several studies have reported that the degree of maternal health benefit is proportional to lactation intensity and duration, suggestive of a dose–response relationship (Gunderson et al, ; Peters et al, ; Ziegler et al, ). The greatest long‐term maternal health benefits have been shown in women who follow the World Health Organization recommendation for exclusive breastfeeding (EBF) for the first 6 months of life without formula supplementation or introduction of other foods or beverages (Organization, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Kramer study (9) did not find any relationship between breastfeeding and cardiovascular health. On the other hand a prospective Study of 300 000 Chinese Women in 2017 in China (7) compared the parous women who had never breastfed with ever breastfeeding and found a significantly lower risk of CVD, with 10% lower risk of coronary heart disease and a 17% lower risk of stroke compared with women who had never breastfed. Each additional six months of breastfeeding per child was associated with a further decrease in risk of coronary heart disease and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Each additional six months of breastfeeding per child was associated with a further decrease in risk of coronary heart disease and stroke. They concluded that a longer duration of breastfeeding was preventive against CVD (7) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 0.5 million Chinese women aged 30 to 79 years from 10 diverse regions across China, history of breastfeeding was associated with a 10% lower risk of cardiovascular disease in later life; this association was stronger among those with a longer duration of breastfeeding (29) . In another study of 1.93 million adults without cardiovascular disease at baseline, light to moderate alcohol use was associated with a reduced risk of death compared to no alcohol consumption at all.…”
mentioning
confidence: 96%